Including access and benefit sharing in the post-2020 Global Biodiversity Framework - Africa Rice Center; Alliance of Bioversity International and CIAT; International Center for Agricultural Research in the Dry Areas; International Crops Research Institute for the Semi-Arid Tropics; International Institute of Tropical Agriculture; International Livestock Research Institute; International Maize and Wheat Improvement Center; International Potato Center; International Rice Research Institute; World Agroforestry Centre; International Treaty on Plant Genetic Resources for Food and Agriculture; United Nations Environment Programme; et al. (2020)
This paper was prepared for consideration by the 2nd meeting of the Open-ended Working Group on the Post-2020 Global Biodiversity Framework, Rome, Italy, February 2020. It includes proposals for how access and benefit-sharing rules, practices and impacts could be integrated in the Post-2020 Global Biodiversity Framework (Post 2020 Framework).